Patterns of failure after resection of extrahepatic bile duct cancer: implications for adjuvant radiotherapy indication and treatment volumes - Choi, Hoon Sik (Radiat Oncol, 2018)
BACKGROUND: The role of adjuvant radiotherapy (RT) and setting proper RT target volumes have not been clearly demonstrated for extrahepatic bile duct (EHBD) cancer, due to the rarity of the disease and the lack of randomized trials. This study was conducted to evaluate the indication and treatment volume for adjuvant RT in EHBD cancer patients by identifying the prognostic factors for loco-regional (LR) failure, and analyze the patterns of LR failure. METHODS: Ninety-three patients with EHBD cancer, who underwent resection without adjuvant RT, at 2 medical centers, between 2001 and 2016, were analyzed retrospectively. Univariable and multivariable analyses were performed to find the prognostic factors for LR recurrence. The initial patterns of failure were recorded, especially those of LR recurrence, and categorized according to the Japanese classification. RESULTS: The median follow-up duration was 30 months, and 38 (40.9%) patients experienced LR recurrence during this period. With regards to LR recurrence, close or positive resection margin (RM) status (p < 0.001) remained statistically significant in the multivariable analysis. The most common LR recurrence sites were the tumor bed (18.3%), and lymph node (LN) stations No. 8 (14.1%), No. 9 (12.7%), No. 12 (12.7%), No. 13 (5.6%), No. 14 (21.1%), No. 16 (14.1%), and No. 17 (1.4%). CONCLUSIONS: A close or positive RM status may be suggestive of high LR recurrence rates. In such cases, adjuvant RT may improve outcomes. When adjuvant RT is performed, the treatment volume should be well-designed so as to encompass the tumor bed, as well as LN stations No. 8, No. 9, No. 12, No. 14, and No. 16. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13014-018-1024-z) contains supplementary material, which is available to authorized users.